Alveolar Fluid Clearance in Pathologically Relevant Conditions: In Vitro and In Vivo Models of Acute Respiratory Distress Syndrome - Huppert, Laura A.; Matthay, Michael A. (Frontiers in Immunology, 2017)
Critically ill patients with respiratory failure from Acute Respiratory Distress Syndrome (ARDS) have reduced ability to clear alveolar edema fluid. This reduction in alveolar fluid clearance (AFC) contributes to the morbidity and mortality in ARDS. Thus, it is important to understand why AFC is reduced in ARDS in order to design targeted therapies. In this review, we highlight experiments that have advanced our understanding of ARDS pathogenesis, with particular reference to the alveolar epithelium. First, we review how vectorial ion transport drives the clearance of alveolar edema fluid in the uninjured lung. Next, we describe how alveolar edema fluid is less effectively cleared in lungs affected by ARDS, and describe selected in vitro and in vivo experiments that have elucidated some of the molecular mechanisms responsible for the reduced AFC. Finally, we describe one potential therapy that targets this pathway: bone marrow derived mesenchymal stem (stromal) cells (MSCs). Based on pre-clinical studies, MSCs enhance alveolar fluid clearance and promote the resolution of pulmonary edema, and thus may offer a promising cell-based therapy for ARDS.